2004
DOI: 10.1111/j.1529-8817.2004.03164.x
|View full text |Cite
|
Sign up to set email alerts
|

AUXOSPORE FORMATION AND THE MORPHOLOGY OF THE INITIAL CELL OF THE MARINE ARAPHID DIATOM GEPHYRIA MEDIA (BACILLARIOPHYCEAE)1

Abstract: Recent studies have led to a rapid increase in knowledge of auxospore formation in diatoms. However, these studies have been limited to centric and raphid pennate diatoms, and there is still very little information for the araphid pennate diatoms. Using LM and SEM, we studied the development of the auxospore and the initial cell of the marine epiphytic diatom Gephyria media Arnott. Auxospores were bipolar and curved in side view, as in many other pennate diatoms. SEM revealed many transverse perizonial bands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 14 publications
3
40
0
Order By: Relevance
“…Additionally, transverse perizonial bands, as in Diprora, are also found in many raphid pennates (Mann et al, 2011). The perizonium structure for some non-raphid pennates is quite different from the condition observed in Diprora (Sato et al, 2004(Sato et al, , 2008. Finally, a close relationship between Diprora and members of the Sellaphoraceae is consistent with the presence in both of hymenate occlusions (Round et al, 1990) and a single H-shaped chloroplast lying against the epivalve (Mann, 1989).…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, transverse perizonial bands, as in Diprora, are also found in many raphid pennates (Mann et al, 2011). The perizonium structure for some non-raphid pennates is quite different from the condition observed in Diprora (Sato et al, 2004(Sato et al, , 2008. Finally, a close relationship between Diprora and members of the Sellaphoraceae is consistent with the presence in both of hymenate occlusions (Round et al, 1990) and a single H-shaped chloroplast lying against the epivalve (Mann, 1989).…”
Section: Discussionsupporting
confidence: 53%
“…A polar cap, presumably representing the ruptured remains of the original zygote wall, covered the auxospore endings (Figs 22,28,arrowhead). Scales (Sato et al, 2004;Kaczmarska et al, 2007) or other incunabula (e.g. the strip-like elements outside the perizonium in Nitzschia fonticola: Trobajo et al, 2006), could not be detected.…”
Section: Sexual Processmentioning
confidence: 99%
“…Mann, 1989). The perizonium of our E. bilunaris is thus more akin to that of the araphid pennate diatoms Rhabdonema (von Stosch, 1962) and Gephyria (Sato et al, 2004), where the central band is likewise split, than it is to most raphid diatoms. Clearly, many more araphid pennates need to be studied in detail before conclusions can be drawn, but it is unlikely a priori that the primary band would become a complete hoop until after the evolution of the raphe, since it would be difficult for essentially non-motile araphid pennate diatoms to escape from an auxospore casing constrained by a complete band around its centre.…”
Section: Correspondence Between Molecular and Mating Datamentioning
confidence: 89%
“…42 (arrowhead) is homologous with the longitudinal perizonium present in some other pennate diatoms (e.g. von Stosch, 1962Stosch, , 1982Mann, 1982;Sato et al, 2004). In E. arcus Ehrenberg, Geitler (1951) described a perizonium of rings and reported that the perizonium was broken apart during formation of the initial cells (op.…”
Section: Correspondence Between Molecular and Mating Datamentioning
confidence: 99%
See 1 more Smart Citation